Effectiveness of the Usage of Various Solvent in Essential Oil Production from Tuberose Flower Waste (Polianthes Tuberose L.) by Enfleurage Method - Nugrahini, Arita Dewi; Baskara, Candra Dewa; ., Jumeri; Ainuri, Makhmudun (KnE Life Sciences, 2016)
Tuberose flower wastes are potentially used as raw materials for producing essential oils. Enfleurage method was used in the extraction process of the flower wastes. Petroleum ether and hexane were used as solvents during the extraction, while snow white (white butter) was used as fat during the enfleurage process. The enfleurage process was done for 4 days with replacement of flowers every 24 hours. It was found that petroleum ether gave higher yield than hexane (i.e. 7.07%). However, compared with hexane, petroleum ether was still existed on the produced essential oil. Keywords: enfleurage, hexane, petroleum ether, tuberose flower, waste